Networks of Care: an approach to improving maternal and newborn health - Kalaris, K; Radovich, E; Carmone, AE; Smith, JM; Hyre, A; Baye, ML; Vougmo, C; Banerjee, A; Liljestrand, J; Moran, AC (Johns Hopkins School Bloomberg School of Public Health, Center for Communication Programs, 2022)
Networks of Care (NOCs) can improve quality of care, continuity of care, and maternal and newborn outcomes. They focus on relational elements that are key to health system functioning and are context specific. NOCs focus on creating intentional connections between people and services and strengthening the functional aspects of health systems while incorporating and emphasizing core relational aspects. They can also be used to strengthen referral systems, thus promoting continuity of care. With momentum and interest gathering around the NOC approach, it could be an essential tool for meeting the Sustainable Development Goals for maternal and newborn health.